2014
DOI: 10.1089/big.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Tire Changes, Fresh Air, and Yellow Flags: Challenges in Predictive Analytics for Professional Racing

Abstract: Our goal is to design a prediction and decision system for real-time use during a professional car race. In designing a knowledge discovery process for racing, we faced several challenges that were overcome only when domain knowledge of racing was carefully infused within statistical modeling techniques. In this article, we describe how we leveraged expert knowledge of the domain to produce a real-time decision system for tire changes within a race. Our forecasts have the potential to impact how racing teams c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The work done by Tulabandhula et al [34] comes closest to what is pursued in this paper. Using ML methods, they predict the change in position during the next outing (equal to a stint) in NASCAR races on the basis of the number of tires changed in the preceding pit stop.…”
Section: Motorsportmentioning
confidence: 69%
See 2 more Smart Citations
“…The work done by Tulabandhula et al [34] comes closest to what is pursued in this paper. Using ML methods, they predict the change in position during the next outing (equal to a stint) in NASCAR races on the basis of the number of tires changed in the preceding pit stop.…”
Section: Motorsportmentioning
confidence: 69%
“…This is surprising, considering the amount of money and data in the sport. The work done by Tulabandhula et al [34] comes closest to our target. However, it is not applicable in our case, since their algorithm does not predict whether the driver should make a pit stop.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Deep learning-based forecasting has observed its success across domains, including: demand prediction [20], traffic prediction [21], clinical state progression prediction [25], epidemic forecasting [8], etc. However, when addressing the forecasting problem in the specific domain of motorsports, we found that the state-of-the-art models in this field are simulation methods or machine learning methods, all highly rely on the domain knowledge [1], [12], [17], [30]. Simply applying a deep learning model here does not deliver better forecasting performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is very much similar to our work-flow, where they used the combination of previous data and in game data to predict a pitchers performance. Tulabandhula and Rudin (2014) were designed a real time prediction and decision system for professional car racing. Model makes the decision of when is the best time for tire change and how many of them.…”
Section: Introductionmentioning
confidence: 99%